2015
DOI: 10.3390/molecules20058499
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Novel Pyrazolo[3,4-g][1,8]naphthyridin-5-amine with Potential Antifungal and Antitumor Activity

Abstract: Abstract:The microwave assisted reaction between heterocyclic o-aminonitriles 1 and cyclic ketones 2 catalyzed by zinc chloride led to new series of pyrazolo [3,4-b] [1,8]naphthyridin-5-amines 3 in good yields. This procedure provides several advantages such as being environmentally friendly, high yields, simple work-up procedure, broad scope of applicability and the protocol provides an alternative for the synthesis of pyrazolonaphthyridines. The whole series showed antifungal activities against Candida alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Novel compounds for treatment - The synthesis of novel compounds has been explored by one research group in Colombia ( Acosta et al 2015 , Ramírez et al 2015 , Montoya et al 2016 , Ramírez-Prada et al 2017 ) and by two Brazilian groups (da Silva et al 2016 , Palanco et al 2017 ) and their preliminary results look promising. Pyrazolonaphthyridines ( Acosta et al 2015 ), thiazole-based pyrimido[4,5-b] [1,4] diazepines ( Ramírez et al 2015 ), chalcones and N-aryl-2-pyrazolines ( Montoya et al 2016 ), and quinolone-based pyrazoles ( Ramírez-Prada et al 2017 ) have shown antifungal activity not only against C. neoformans but also against Candida albicans , with some of them showing fungicidal, rather than fungistatic activity, which makes them good antifungal candidates.…”
mentioning
confidence: 99%
“…Novel compounds for treatment - The synthesis of novel compounds has been explored by one research group in Colombia ( Acosta et al 2015 , Ramírez et al 2015 , Montoya et al 2016 , Ramírez-Prada et al 2017 ) and by two Brazilian groups (da Silva et al 2016 , Palanco et al 2017 ) and their preliminary results look promising. Pyrazolonaphthyridines ( Acosta et al 2015 ), thiazole-based pyrimido[4,5-b] [1,4] diazepines ( Ramírez et al 2015 ), chalcones and N-aryl-2-pyrazolines ( Montoya et al 2016 ), and quinolone-based pyrazoles ( Ramírez-Prada et al 2017 ) have shown antifungal activity not only against C. neoformans but also against Candida albicans , with some of them showing fungicidal, rather than fungistatic activity, which makes them good antifungal candidates.…”
mentioning
confidence: 99%
“…A reaction of 2-(2-phenyl-1,8-naphthyridin-3-yl)isoindoline-1,3-dione (1) with hydrazine monohydrate in alcohol to give 2-phenyl-1,8-naphthyridin-3-amine (2).…”
Section: Resultsmentioning
confidence: 99%
“…The 1,8-naphthyridine scaffold is a centre of attention in all the nitrogen containing heterocycles due to their biological importance. The significant activities of these compounds have been reported such as antibacterial [1], antifungal and antitumor [2], antihypertensive [3], HIV-1 integrase mutant [4], antiplatelet [5], antidepressant [6], DNA stabilizing [7], antiallergic [8] activities, etc. Moreover, 2-iminothiazolidinone is a privileged moiety in five-membered heterocyclic system and its derivatives exhibited a large range of interesting bioactivities like antibiofilm [9], S1P1 receptor agonist [10], antithrombotic [11] antibacterial [12], anticancer [13] activities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Acosta et al [45] synthesize various 1, 8-naphthyridine derivatives by microwave-assisted synthesis with heterocyclic o-aminonitriles and cyclic ketenes catalyzed by ZnCl2 and produce a series of pyrazolo [3,4-b] [1,8] naphthyridine-5-amines. The derivatives with a 4-p-tolyl substituent at naphthyridine skeleton (35a, 35b and 35c) are most active against C. albicans, which appear to be linked with their corresponding hydrophobicity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%